Differential bone preservation models in Middle and Lower Paraná River Basin based on physicochemical properties of soils - Galligani, Paula Elisabet (Facultad de Filosofía y Humanidades. Museo de Antropología, 2023)
In the east-central portion of the Santa Fe province (San Jerónimo, La Capital and Las Colonias Departments) poor bone preservation is a characteristic feature of the regional archaeological record. Therefore, during the last decade, a study of bone diagenesis at different bone levels has been under development. Part of this research was focused on the construction of predictive spatial models of bone preservation based on the analysis of specific properties of soils using geographic information systems (GIS). These models have been evaluated with information obtained from the analysis of bone remains recovered from regional archaeological sites. On this basis, this paper presents and discusses new predictive maps for a broader coverage area, which includes the Middle and Lower Paraná River basin (Santa Fe, Entre Ríos and Buenos Aires provinces). The aim is to provide an appropriate interpretative framework to discuss the variation in bone preservation conditions in the south of the Litoral region of Argentina.